Serum Calcium Increase Correlates With Worsening of Lipid Profile: An Observational Study on a Large Cohort From South Italy. Issue 8 (February 2016) - Gallo, Luigia; Faniello, Maria C.; Canino, Giovanni; Tripolino, Cesare; Gnasso, Agostino; Cuda, Giovanni; Costanzo, Francesco S.; Irace, Concetta
Abstract : Abstract: Despite the well-documented role of calcium in cell metabolism, its role in the development of cardiovascular disease is still under heavy debate. Several studies suggest that calcium supplementation might be associated with an increased risk of coronary heart disease, whereas others underline a significant effect on lowering high blood pressure and hyperlipidemia. The purpose of this study was to investigate, in a large nonselected cohort from South Italy, if serum calcium levels correlate with lipid values and can therefore be linked to higher individual cardiovascular risk. Eight-thousand-six-hundred-ten outpatients addressed to the Laboratory of Clinical Biochemistry, University of Magna Græcia, Catanzaro, Italy from January 2012 to December 2013 for routine blood tests, were enrolled in the study. Total HDL-, LDL- and non-HDL colesterol, triglycerides, and calcium were determined with standard methods. We observed a significant association between total cholesterol, LDL-cholesterol, HDL-cholesterol, non-HDL cholesterol, triglycerides, and serum calcium in men and postmenopause women. Interestingly, in premenopause women, we only found a direct correlation between serum calcium, total cholesterol, and HDL-cholesterol. Calcium significantly increased while increasing total cholesterol and triglycerides in men and postmenopause women. Our results confirm that progressive increase of serum calcium level correlates with worsening of lipid profile in our study population. Therefore, we suggest that a greater caution should be used in calcium supplement prescription particularly in men and women undergoing menopause, in which an increase of serum lipids is already known to be associated with a higher cardiovascular risk.